Anti-aging polypropylene composite material as well as preparation method and application thereof

By modifying the synergistic effect of titanium dioxide and anhydrous calcium sulfate whiskers and polypropylene, an anti-aging polypropylene composite material is formed, which solves the problem of poor anti-aging performance in the prior art, and significantly improves the mechanical properties and thermal stability of the material .

CN119176984APending Publication Date: 2024-12-24GUANGDONG LABORATORY OF CHEMISTRY & FINE CHEMICAL IND JIEYANG CENTER JIEYANG +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411437830.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The anti-aging and mechanical properties of existing anti-aging polypropylene composite materials are poor, mainly because the existing processes only use physical composites, resulting in the decline in the performance of the material under long-term aging and high temperatures.

Method used

By modifying titanium dioxide and anhydrous calcium sulfate whiskers with silane coupling agent and melt blending, refining, crushing and injection molding with polypropylene, a coordinated UV shielding and mesh structure is formed to improve the anti-aging and mechanics of the material. performance.

Benefits of technology

The polypropylene composite material has achieved good mechanical properties after aging for a long time, and has significantly improved its thermal stability and interface compatibility, prolonged the crystallization induction period, and increased the crystallization rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176984A_ABST
    Figure CN119176984A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-aging polypropylene composite material as well as a preparation method and application thereof, and belongs to the technical field of polypropylene material preparation. The preparation method of the anti-aging polypropylene composite material provided by the invention comprises the following steps: adding titanium dioxide, a KH-570 silane coupling agent and sodium dodecyl benzene sulfonate into a mixed aqueous solution of acrylonitrile and azodiisobutyronitrile for reaction to obtain modified titanium dioxide; the preparation method comprises the following steps: adding anhydrous calcium sulfate whiskers, a KH-570 silane coupling agent and sodium dodecyl benzene sulfonate into a mixed aqueous solution of acrylonitrile and azodiisobutyronitrile for reaction to obtain modified calcium sulfate; the modified titanium dioxide, the modified calcium sulfate and the polypropylene are sequentially subjected to melt blending, banburying, smashing and injection molding, and the anti-aging polypropylene composite material is obtained. The polypropylene composite material can be endowed with excellent anti-aging performance, mechanical performance and thermal stability, and has wide application prospects in preparation of plastic products, automobile parts, wire and cable insulating layers, furniture, children toys and garbage cans.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of polypropylene material preparation, and in particular relates to an anti-aging polypropylene composite material and a preparation method and application thereof. Background Art

[0002] Polypropylene is a thermoplastic resin obtained by polymerization of propylene and is one of the main raw materials for plastic products. However, as a raw material for plastic products, polypropylene has the defects of unstable mechanical and physical and chemical properties, as well as defects in anti-aging and thermal stability. At present, the anti-aging performance of polypropylene is generally modified by adding stabilizers, antioxidants and toughening agents. However, the existing composite process only achieves performance modification through physical composite, resulting in poor anti-aging performance. Therefore, it is necessary to optimize the modification process to improve the comprehensive performance of polypropylene.

[0003] The prior art with application publication number CN 107365447 A discloses an anti-aging polypropylene composite material, which is prepared by compounding 80 parts by weight of polypropylene raw material, 20-25 parts by weight of reinforcement, 3-6 parts by weight of stabilizer, 5-8 parts by weight of antioxidant, 2-4 parts by weight of toughening agent and 1-3 parts by weight of coupling agent.

[0004] However, the existing anti-aging polypropylene composite materials are only prepared by physical compounding, which results in poor anti-aging performance and poor mechanical properties. Summary of the invention

[0005] The present application discloses an anti-aging polypropylene composite material and a preparation method and application thereof, aiming to solve the technical problems of poor anti-aging performance and poor mechanical properties of existing anti-aging polypropylene composite materials.

[0006] In order to achieve the above purpose, the technical solution of this application is:

[0007] The first aspect of the present application provides a method for preparing an anti-aging polypropylene composite material, the method comprising:

[0008] Adding titanium dioxide, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate into a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile to react, thereby obtaining modified titanium dioxide;

[0009] Anhydrous calcium sulfate whiskers, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate are added into a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile to react and obtain modified calcium sulfate;

[0010] The modified titanium dioxide, the modified calcium sulfate and polypropylene are sequentially melt-blended, banburyed, crushed and injection-molded to obtain an anti-aging polypropylene composite material.

[0011] In combination with the first aspect, preferably, the mass ratio of titanium dioxide, KH-570 silane coupling agent and acrylonitrile added is 4-6:3:670.

[0012] In combination with the first aspect, preferably, the mass ratio of the anhydrous calcium sulfate whisker, KH-570 silane coupling agent and acrylonitrile added is 1-3:1:134.

[0013] In combination with the first aspect, preferably, the added mass ratio of the modified titanium dioxide, modified calcium sulfate and polypropylene is 1-7:3:100.

[0014] In combination with the first aspect, preferably, when titanium dioxide, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate are added to a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile for reaction, the temperature is 70-90° C. and the reaction time is 1-3 h.

[0015] In combination with the first aspect, preferably, when anhydrous calcium sulfate whiskers, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate are added to a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile for reaction, the temperature is 70-90° C. and the reaction time is 1-3 h.

[0016] In combination with the first aspect, preferably, the kneading temperature is 150-200°C.

[0017] In combination with the first aspect, preferably, the injection molding temperature is 200-220°C.

[0018] The second aspect of the present application provides an anti-aging polypropylene composite material prepared by the preparation method described in the first aspect.

[0019] The third aspect of the present application provides the use of the anti-aging polypropylene composite material described in the second aspect in the preparation of plastic products, automobile parts, wire and cable insulation layers, furniture, children's toys, and trash cans.

[0020] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0021] The preparation method provided by the present application is an anti-aging polypropylene composite material made of titanium dioxide modified by silane coupling agent and propylene group, anhydrous calcium sulfate whisker modified by silane coupling agent and propylene group and polypropylene. On the one hand, the modified titanium dioxide and modified anhydrous calcium sulfate whisker play a synergistic ultraviolet shielding effect, which can give polypropylene excellent anti-aging performance, and still show good mechanical properties after aging for 1000h; on the other hand, the synergistic effect of modified titanium dioxide and modified anhydrous calcium sulfate whisker can form a dense network structure to accelerate the transmission of impact energy, and improve the interfacial compatibility with polypropylene, thereby greatly improving the mechanical properties of the composite material; finally, the composite material can produce a variety of crystal forms, and the crystallization induction period is shortened and the crystallization rate is accelerated under the action of a variety of crystal forms, so that it has excellent thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 Scanning electron microscope images of the fracture surfaces of the B1-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material prepared in the examples of the present application after aging for 1000 hours;

[0024] Among them, a) B1-polypropylene composite material, b) A1-anti-aging polypropylene composite material, c) A10-anti-aging polypropylene composite material, d) A11-anti-aging polypropylene composite material, d) A12-anti-aging polypropylene composite material;

[0025] Figure 2 Impact strength diagrams of B1-9-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material prepared in the examples of the present application;

[0026] Figure 3 The bending strength diagrams of B1-9-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material prepared in the examples of the present application;

[0027] Figure 4The bending elastic modulus diagrams of B1-9-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material were prepared for the examples of the present application;

[0028] Figure 5 The tensile strength diagrams of B1-9-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material prepared for the embodiments of the present application;

[0029] Figure 6 TG and DTG graphs of B9-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material prepared in the examples of the present application;

[0030] Figure 7 DSC graphs of B9-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material prepared in the examples of the present application. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0032] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0033] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0034] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0035] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0036] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0037] In a first aspect, an embodiment of the present application provides a method for preparing an anti-aging polypropylene composite material, the method comprising:

[0038] Adding titanium dioxide, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate into a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile to react, thereby obtaining modified titanium dioxide;

[0039] Anhydrous calcium sulfate whiskers, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate are added into a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile to react and obtain modified calcium sulfate;

[0040] The modified titanium dioxide, the modified calcium sulfate and polypropylene are sequentially melt-blended, banburyed, crushed and injection-molded to obtain an anti-aging polypropylene composite material.

[0041] Among them, on the one hand, the synergistic UV shielding effect of modified titanium dioxide and modified anhydrous calcium sulfate whiskers can give polypropylene excellent anti-aging properties, and still show good mechanical properties after aging for 1000 hours; on the other hand, the synergistic effect of modified titanium dioxide and modified anhydrous calcium sulfate whiskers can form a dense network structure to accelerate the transmission of impact energy, and improve the interfacial compatibility with polypropylene, thereby greatly improving the mechanical properties of the composite material; finally, the composite material can produce a variety of crystal forms, under the action of a variety of crystal forms, the crystallization induction period is shortened, the crystallization rate is accelerated, and it has excellent thermal stability.

[0042] In the embodiment of the present application, the added mass ratio of the titanium dioxide, KH-570 silane coupling agent and acrylonitrile is preferably 4-6:3:670, and more preferably 5:3:670. Among them, the nano-TiO2 particles have the advantages of being non-toxic, tasteless, and having a large refractive index, having strong visible light transmittance, having good scattering and ultraviolet absorption capabilities, and can be used as ultraviolet shielding agents. After absorbing ultraviolet rays, they do not decompose or change color, and have good stability. By controlling the mass ratio of titanium dioxide, KH-570 silane coupling agent and acrylonitrile, a free radical polymerization method is used to form more hydroxyl groups on the surface of the inorganic filler, and the silane coupling agent is grafted onto the surface of titanium dioxide, so that acrylonitrile is grafted onto the surface. Nano-titanium dioxide has a good ultraviolet shielding effect, and polyacrylonitrile also shows good light resistance. Through the synergistic effect of the two, not only can an anti-aging effect be produced, but also the mechanical properties of polypropylene can be enhanced.

[0043]

[0044] In the embodiment of the present application, the added mass ratio of the anhydrous calcium sulfate whisker, KH-570 silane coupling agent and acrylonitrile is preferably 1-3:1:134, and more preferably 2:1:134. Among them, the anhydrous calcium sulfate whisker is a fibrous single crystal with a complete appearance and internal structure. CSW has the lowest price and has the advantages of high strength and high modulus compared to other fibers. It can be used for the reinforcement and modification of plastics and polymer materials. It is a non-toxic green material. By controlling the amount of each substance added, acrylonitrile can be evenly and stably grafted on the surface of the anhydrous calcium sulfate whisker.

[0045]

[0046] In the embodiment of the present application, the added mass ratio of the modified titanium dioxide, modified calcium sulfate and polypropylene is preferably 1-7:3:100. Among them, by controlling the added amount of modified titanium dioxide, when the added amount is 3%, the polypropylene composite material has the best mechanical properties, anti-aging properties and thermal stability.

[0047] In the embodiment of the present application, when titanium dioxide, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate are added to a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile for reaction, the temperature is preferably 60-100° C. and the reaction time is preferably 1-3 hours.

[0048] In the embodiment of the present application, when anhydrous calcium sulfate whiskers, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate are added to a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile for reaction, the temperature is preferably 60-100° C. and the reaction time is preferably 1-3 hours.

[0049] In the second aspect, the present application also provides an anti-aging polypropylene composite material prepared by the preparation method described in the first aspect. The preparation method of the present application can give the polypropylene composite material excellent anti-aging performance, mechanical properties, and thermal stability.

[0050] The third aspect of the present application provides the use of the anti-aging polypropylene composite material described in the second aspect in the preparation of plastic products, automobile parts, wire and cable insulation layers, furniture, children's toys, and trash cans. Among them, based on the excellent anti-aging performance, mechanical properties, and thermal stability of the above-mentioned polypropylene composite material, it can give the product excellent product competitiveness and has a wide range of application prospects.

[0051] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0052] Example 1

[0053] This embodiment provides a method for preparing an A1-anti-aging polypropylene composite material, which specifically includes:

[0054] S101: Dissolve 2g of titanium dioxide in 50mL of anhydrous ethanol and 10mL of deionized water, adjust the pH to neutral, add 1.2g of KH570 silane coupling agent, react at 80°C for 1h, add 0.26g of sodium dodecylbenzene sulfonate, 134g of acrylonitrile (AN) and 1.34g of azobisisobutyronitrile (AIBN), react for 2h, take out the product, centrifuge and wash it with an ethanol / water mixture, and dry it in an oven at 100°C for 8h to obtain A1-modified titanium dioxide with a grafting rate of 55.72G;

[0055] S102: 2 g of anhydrous calcium sulfate whiskers, 1 g of KH570 silane coupling agent and 60 ml of anhydrous ethanol were reacted at 80°C for 1 h, 0.26 g of sodium dodecylbenzene sulfonate, 134 g of acrylonitrile (AN) and 1.34 g of azobisisobutyronitrile (AIBN) were added, and the product was taken out after reacting for 2 h, centrifuged and washed with an ethanol / water mixture, and dried in an oven at 100°C for 8 h to obtain A1-modified anhydrous calcium sulfate whiskers with a grafting rate of 49.23G;

[0056] S103: Mix modified titanium dioxide, modified anhydrous calcium sulfate whiskers and polypropylene, with the proportion of modified titanium dioxide being 3%. Set the temperature to 180°C, heat and stir evenly in an internal mixer after discharging the materials, then put the mixed samples into a strong crusher to crush them into a material of uniform coarseness and fineness, and put them into an oven at 60°C for drying. Finally, put them into an injection molding machine and mold them into dumbbell-shaped and round splines. Before injection molding, set the melt temperature to 200°C and the injection pressure to 100MPa to obtain an A1-anti-aging polypropylene composite material (A1-PP / TiO2-PAN / CSW-PAN).

[0057] Example 2

[0058] This embodiment provides a preparation method for an A2-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that in the first step of this embodiment, the temperature of the modified titanium dioxide is 60°C, the grafting rate of the A2-modified titanium dioxide is 14.68G, and an A2-anti-aging polypropylene composite material is obtained.

[0059] Example 3

[0060] This embodiment provides a preparation method for an A3-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that the temperature of the modified titanium dioxide in the first step of this embodiment is 70° C., the grafting rate of the A3-modified titanium dioxide is 35.74G, and an A3-anti-aging polypropylene composite material is obtained.

[0061] Example 4

[0062] This embodiment provides a preparation method for an A4-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that the temperature of the modified titanium dioxide in the first step of this embodiment is 90° C., the grafting rate of the A4-modified titanium dioxide is 43.12G, and an A4-anti-aging polypropylene composite material is obtained.

[0063] Example 5

[0064] This embodiment provides a preparation method for an A5-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that in the first step of this embodiment, the temperature of the modified titanium dioxide is 100°C, the grafting rate of the A5-modified titanium dioxide is 36.85G, and an A5-anti-aging polypropylene composite material is obtained.

[0065] Example 6

[0066] This embodiment provides a preparation method for an A6-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that in the second step of this embodiment, the temperature of the modified anhydrous calcium sulfate whisker is 60° C., and the grafting rate of the A6-modified anhydrous calcium sulfate whisker is 24.69G, thereby obtaining an A6-anti-aging polypropylene composite material.

[0067] Example 7

[0068] This embodiment provides a preparation method for A7-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that the temperature of the modified anhydrous calcium sulfate whisker in the second step of this embodiment is 70°C, the grafting rate of the A7-modified anhydrous calcium sulfate whisker is 37.82G, and the A7-anti-aging polypropylene composite material is obtained.

[0069] Example 8

[0070] This embodiment provides a preparation method for A8-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that the temperature of the modified anhydrous calcium sulfate whisker in the second step of this embodiment is 90°C, the grafting rate of the A8-modified anhydrous calcium sulfate whisker is 21.57G, and the A8-anti-aging polypropylene composite material is obtained.

[0071] Example 9

[0072] This embodiment provides a preparation method for A9-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that the temperature of the modified anhydrous calcium sulfate whisker in the second step of this embodiment is 100°C, the grafting rate of the A9-modified anhydrous calcium sulfate whisker is 11.66G, and the A9-anti-aging polypropylene composite material is obtained.

[0073] Example 10

[0074] This embodiment provides a preparation method for an A10-anti-aging polypropylene composite material. The component ratio, preparation operation, and process parameters are basically the same as those in Example 1, except that in this embodiment, modified titanium dioxide, modified anhydrous calcium sulfate whiskers, and polypropylene are mixed, and the modified titanium dioxide accounts for 1% to obtain an A10-anti-aging polypropylene composite material.

[0075] Embodiment 11

[0076] This embodiment provides a preparation method for an A11-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that in this embodiment, modified titanium dioxide, modified anhydrous calcium sulfate whiskers and polypropylene are mixed, and the proportion of modified titanium dioxide is 5%, to obtain an A11-anti-aging polypropylene composite material.

[0077] Example 12

[0078] This embodiment provides a preparation method for an A12-anti-aging polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those in Example 1, except that in this embodiment, modified titanium dioxide, modified anhydrous calcium sulfate whiskers and polypropylene are mixed, and the proportion of modified titanium dioxide is 7%, to obtain an A12-anti-aging polypropylene composite material.

[0079] At the same time, in order to verify the comprehensive performance of the anti-aging polypropylene composite material prepared in the above examples, the present application provides the following comparative examples for detailed description.

[0080] Comparative Example 1

[0081] This comparative example provides a preparation method of a B1-polypropylene composite material (B1-PP / TiO2-PAN), which specifically includes:

[0082] S201: Dissolve 2g of titanium dioxide in 50mL of anhydrous ethanol and 10mL of deionized water, adjust the pH to neutral, add 1.2g of KH570 silane coupling agent, react at 80°C for 1h, add 0.26g of sodium dodecylbenzene sulfonate, 134g of acrylonitrile (AN) and 1.34g of azobisisobutyronitrile (AIBN), react for 2h, take out the product, centrifuge and wash it with an ethanol / water mixture, and dry it in an oven at 100°C for 8h to obtain A1-modified titanium dioxide with a grafting rate of 55.72G;

[0083] S202: Mix modified titanium dioxide and polypropylene, with the proportion of modified titanium dioxide being 3%. Set the temperature to 180°C, heat and stir evenly in an internal mixer after discharging the material, then put the mixed sample into a high-powered crusher to crush it into a material of uniform coarseness and fineness, and put it into an oven at 60°C for drying. Finally, put it into an injection molding machine and mold it into dumbbell-shaped and round strips. Before injection molding, set the melt temperature to 200°C and the injection pressure to 100MPa to obtain a B1-polypropylene composite material (B1-PP / TiO2-PAN).

[0084] Comparative Example 2

[0085] This comparative example provides a preparation method of a B2-polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those of comparative example 1, except that in this comparative example, modified titanium dioxide and polypropylene are mixed, and the proportion of modified titanium dioxide is 1%, to obtain a B2-polypropylene composite material.

[0086] Comparative Example 3

[0087] This comparative example provides a preparation method for a B3-polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those of comparative example 1, except that in this comparative example, modified titanium dioxide and polypropylene are mixed, and the proportion of modified titanium dioxide is 5%, to obtain a B3-polypropylene composite material.

[0088] Comparative Example 4

[0089] This comparative example provides a preparation method of a B4-polypropylene composite material. The component ratio, preparation operation and process parameters are basically the same as those of comparative example 1, except that in this comparative example, modified titanium dioxide and polypropylene are mixed, and the proportion of modified titanium dioxide is 7%, to obtain a B4-polypropylene composite material.

[0090] Comparative Example 5

[0091] This comparative example provides a preparation method of a B5-polypropylene composite material (B5-PP / CSW-PAN), which specifically includes:

[0092] S301: 2 g of anhydrous calcium sulfate whiskers, 1 g of KH570 silane coupling agent and 60 ml of anhydrous ethanol were reacted at 80°C for 1 h, 0.26 g of sodium dodecylbenzene sulfonate, 134 g of acrylonitrile (AN) and 1.34 g of azobisisobutyronitrile (AIBN) were added, and the product was taken out after reacting for 2 h, centrifuged and washed with an ethanol / water mixture, and dried in an oven at 100°C for 8 h to obtain A1-modified anhydrous calcium sulfate whiskers;

[0093] S302: Mix modified anhydrous calcium sulfate whiskers and polypropylene, with the proportion of modified titanium dioxide being 3%. Set the temperature to 180°C, heat and stir evenly in an internal mixer after discharging the materials, then put the mixed samples into a high-powered crusher to crush them into a material of uniform coarseness and fineness, and put them into an oven at 60°C for drying. Finally, put them into an injection molding machine and mold them into dumbbell-shaped and round splines. Set the melt temperature to 200°C and the injection pressure to 100MPa before injection molding to obtain a B5-polypropylene composite material (B5-PP / CSW-PAN).

[0094] Comparative Example 6

[0095] This comparative example provides a preparation method for a B6-polypropylene composite material, and the component ratio, preparation operation, and process parameters are basically the same as those of comparative example 5, except that in this comparative example, modified anhydrous calcium sulfate whiskers and polypropylene are mixed, and the proportion of anhydrous calcium sulfate whiskers is 1%, to obtain a B6-polypropylene composite material.

[0096] Comparative Example 7

[0097] This comparative example provides a preparation method of a B7-polypropylene composite material, and the component ratio, preparation operation, and process parameters are basically the same as those of comparative example 5, except that in this comparative example, modified anhydrous calcium sulfate whiskers and polypropylene are mixed, and the proportion of modified anhydrous calcium sulfate whiskers is 5%, to obtain a B7-polypropylene composite material.

[0098] Comparative Example 8

[0099] This comparative example provides a preparation method for a B8-polypropylene composite material, and the component ratio, preparation operation, and process parameters are basically the same as those of comparative example 5, except that in this comparative example, modified anhydrous calcium sulfate whiskers and polypropylene are mixed, and the proportion of modified anhydrous calcium sulfate whiskers is 7%, to obtain a B8-polypropylene composite material.

[0100] Comparative Example 9

[0101] The comparative example of the present application uses pure polypropylene as a comparative example, which is recorded as B9-polypropylene composite material (PP).

[0102] In order to verify the effect of modification temperature on titanium dioxide and anhydrous calcium sulfate whiskers, the reaction was carried out at different temperatures to test the grafting rate of modified titanium dioxide. The test results are shown in Tables 1 and 2.

[0103] Table 1 Grafting rate of modified titanium dioxide at different temperatures

[0104] Serial number Example 2 Example 3 Example 1 Example 4 Example 5 Temperature(℃) 60 70 80 90 100 Grafting rate (G) 14.68 35.74 55.72 43.12 36.85

[0105] Table 2 Grafting rate of modified anhydrous calcium sulfate whiskers at different temperatures

[0106] Serial number Example 6 Example 7 Example 1 Example 8 Example 9 Temperature(℃) 60 70 80 90 100 Grafting rate (G) 24.69 37.82 49.23 21.57 11.66

[0107] According to the test results in Table 1 and Table 2, when the modification temperature is 80°C, the grafting rate of modified titanium dioxide reaches the optimal value, which is crucial to improving the comprehensive performance of polypropylene composites; when the modification temperature is 80°C, the grafting rate of modified anhydrous calcium sulfate whiskers reaches the optimal value, which is also crucial to improving the comprehensive performance of polypropylene composites.

[0108] In order to verify the aging appearance of the anti-aging polypropylene composite material prepared in the embodiment of the present application, a scanning electron microscope test was performed on the anti-aging polypropylene composite material prepared in the embodiment, and the results were as follows: Figure 1 As shown; among them, Figure 1 These are scanning electron microscope images of the fracture surfaces of B1-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material after aging for 1000 hours.

[0109] according to Figure 1As known, the scanning electron microscope images of the fracture surfaces of the B1-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material prepared in the present application after aging for 1000 hours, wherein, a) B1-polypropylene composite material, b) A1-anti-aging polypropylene composite material, c) A10-anti-aging polypropylene composite material, d) A11-anti-aging polypropylene composite material, and d) A12-anti-aging polypropylene composite material, after aging for 1000 hours, obvious cracks appeared in the polypropylene and the surface was damaged to form defects. When the addition amount of modified titanium dioxide was 3%, the surface cracking was significantly reduced, and a very strong interface bonding was observed, which can also be attributed to the synergistic effect between the appropriate amount of modified titanium dioxide and the modified anhydrous calcium sulfate whiskers to enhance the interface adhesion.

[0110] In order to verify the anti-aging performance of the anti-aging polypropylene composite material prepared in the embodiment of the present application, the impact strength, flexural strength, flexural elastic modulus and tensile strength of the anti-aging polypropylene composite material prepared in the embodiment were tested. The results are as follows: Figure 2-Figure 5 shown.

[0111] according to Figure 2-Figure 5 The test results show that, by testing the polypropylene composite materials prepared in the examples and comparative examples, as the amount of modified titanium dioxide added gradually increases, the anti-aging performance of the polypropylene composite materials gradually improves. When the amount of modified titanium dioxide added is 3%, the obtained polypropylene composite material has the best anti-aging performance, but when the amount added continues to increase, the anti-aging performance of the polypropylene composite material gradually decreases. In addition, after aging for 1000 hours, the impact strength of the polypropylene composite material is higher than that of the unaged pure PP material, and its tensile strength is close to that of the unaged pure PP material, proving that PP has not lost its excellent performance. Comparing the mechanical properties of the PP composite materials before and after aging for 1000 hours, the tensile strength of pure PP after aging for 1000 hours is as low as 0.62MPa, while the tensile strength of the A1-anti-aging polypropylene composite material is as high as 19.88MPa, and the impact strength after aging for 1000 hours is higher than that of the unaged pure PP, proving that the addition of modified titanium dioxide and modified anhydrous calcium sulfate whiskers greatly improves the anti-aging performance of PP.

[0112] In order to verify the thermal stability of the anti-aging polypropylene composite material prepared in the examples of the present application, TG, DTG, and DSC tests were performed on the anti-aging polypropylene composite material prepared in the examples. The results were as follows: Figure 6-Figure 7 As shown. Among them, Figure 6 TG and DTG graphs of B9-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material; Figure 7 These are the DSC graphs of B9-polypropylene composite material, A1-anti-aging polypropylene composite material, A10-anti-aging polypropylene composite material, A11-anti-aging polypropylene composite material, and A12-anti-aging polypropylene composite material.

[0113] according to Figure 6 It can be seen that for A1-composite materials, pure PP starts to lose mass at 335°C and the degradation is completed at 485°C. When the addition amount of modified titanium dioxide is 3%, the initial degradation temperature of the anti-aging polypropylene composite material is as high as 435°C, and its residue is about 5.5%, which is higher than pure PP and other composite materials. This proves that the thermal stability of the composite material is the best when the addition amount is 3%, and the thermal stability of all composite materials is better than that of pure PP. With the increase of the addition amount of modified titanium dioxide in DTG, the initial degradation temperature in DTG increases. Due to the presence of nanofillers, it plays a hindering role and inhibits the degradation of PP to the greatest extent.

[0114] according to Figure 7 It can be seen that at the same cooling rate, the crystallization temperature of polypropylene composites with different addition amounts is higher than that of pure PP. This is attributed to the fact that pure PP only has one α crystal form, while the addition of TiO2-PAN and CSW-PAN causes PP to produce multiple crystal forms. Under the action of multiple crystal forms, the crystallization induction period is shortened and the crystallization rate is accelerated. When 3% of modified titanium dioxide is added, the crystallization temperature of the polypropylene composite is the highest, proving that its thermal stability is the best. Adding modified titanium dioxide and modified anhydrous calcium sulfate whiskers to the anti-aging polypropylene composite improves its thermal stability.

[0115] Therefore, the preparation method provided in the present application can give the polypropylene composite material excellent anti-aging properties, mechanical properties, and thermal stability by preparing an anti-aging polypropylene composite material by combining titanium dioxide modified with a silane coupling agent and acryl, anhydrous calcium sulfate whiskers modified with a silane coupling agent and acryl, and polypropylene, and has broad application prospects.

[0116] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0117] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A method for preparing an anti-aging polypropylene composite material, characterized in that: The method comprises: Adding titanium dioxide, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate into a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile to react, thereby obtaining modified titanium dioxide; Anhydrous calcium sulfate whiskers, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate are added into a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile to react and obtain modified calcium sulfate; The modified titanium dioxide, the modified calcium sulfate and polypropylene are sequentially melt-blended, banburyed, crushed and injection-molded to obtain an anti-aging polypropylene composite material.

2. The method for preparing the anti-aging polypropylene composite material according to claim 1, characterized in that: The mass ratio of the titanium dioxide, KH-570 silane coupling agent and acrylonitrile added is 4-6:3:

670.

3. The method for preparing the anti-aging polypropylene composite material according to claim 1, characterized in that: The added mass ratio of the anhydrous calcium sulfate whisker, KH-570 silane coupling agent and acrylonitrile is 1-3:1:

134.

4. The method for preparing the anti-aging polypropylene composite material according to claim 1, characterized in that: The added mass ratio of the modified titanium dioxide, modified calcium sulfate and polypropylene is 1-7:3:

100.

5. The method for preparing the anti-aging polypropylene composite material according to claim 1, characterized in that: When titanium dioxide, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate are added to a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile for reaction, the temperature is 60-100° C. and the reaction time is 1-3 hours.

6. The method for preparing the anti-aging polypropylene composite material according to claim 1, characterized in that: When anhydrous calcium sulfate whiskers, KH-570 silane coupling agent and sodium dodecylbenzene sulfonate are added to a mixed aqueous solution of acrylonitrile and azobisisobutyronitrile for reaction, the temperature is 60-100° C. and the reaction time is 1-3 hours.

7. The method for preparing the anti-aging polypropylene composite material according to claim 1, characterized in that: The temperature of the banburying is 150-200°C.

8. The method for preparing the anti-aging polypropylene composite material according to claim 1, characterized in that: The injection molding temperature is 200-220°C.

9. An anti-aging polypropylene composite material prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the anti-aging polypropylene composite material according to claim 9 in the preparation of plastic products, automobile parts, wire and cable insulation layers, furniture, children's toys, and trash cans.

Citation Information

Patent Citations

  • Anti-aging composite polypropylene material

    CN107365447A

  • Modified polypropylene material and preparation method thereof

    CN117209891A